Factors associated with the incidence of young-onset colorectal cancer: A cross-sectional study - Sianturi, Natallina; Dahlia, Debie; Edison, Chiyar (Narra J, 2025)
The factors associated with the incidence of young-onset colorectal cancer (YO-CRC) remain uncertain and are continuously being studied. The aim of this study was to investigate the factors associated with the incidence of young-onset colorectal cancer. This cross-sectional study examined multiple factors (demographic status, medical comorbidities, smoking, alcohol intake, nighttime sleep duration, family history of cancer, sedentary behavior, daily consumption of fried foods, fast food, and processed meat) among 171 patients from two cancer referral hospitals in Jakarta, Indonesia. Logistic regression analysis revealed that the low-income group had a higher risk of YO-CRC compared to high-income group (p=0.004). Those with comorbid diseases such as inflammatory bowel disease, diabetes, or high cholesterol were more likely to develop YO-CRC compared to those without these conditions (p=0.002). Frequent consumption of processed meat (vs seldom) (p=0.003) and fried food (vs no consumption) (p=0.001) were associated with higher risk. Those with high sedentary behavior (vs low) (p=0.021) also had higher risk of YO-CRC. Notably, nighttime sleep emerged as the strongest predictor (odds ratio (OR): 10.462). These findings underscore the need for targeted public health interventions promoting adequate sleep, healthy diets, and active lifestyles, particularly among Indonesian youth and low-income groups. Further studies are recommended to investigate these associations in larger and more diverse populations across Indonesia.